Development of a Method to Detect Humans and Their Motion Based On a Self-Supervised Learning Method: A Comprehensive Review - Naina Devi,; Mrs Vanita Jilowa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive review paper examines the recent advancements in human detection and motion analysis using self-supervised learning methods. Traditional approaches for human motion understanding have largely relied on supervised learning techniques that require extensive labeled datasets, which are costly and time-consuming to acquire. The emergence of self-supervised learning paradigms has revolutionized this field by enabling models to learn meaningful representations from unlabeled data. This review systematically analyzes the evolution from traditional optical flow methods and pose-based approaches to modern self-supervised frameworks, with particular focus on the groundbreaking H-MoRe (Human Motion Representation) method. We explore the technical foundations, architectural innovations, and performance benchmarks across multiple applications including gait recognition, action recognition, and video generation. The comprehensive analysis covers performance metrics, comparative evaluations, and practical implementations across diverse datasets including CASIA-B, Diving48, and UTD-MHAD. The paper also discusses current challenges, future research directions, and the potential impact of these methods on various real-world applications in healthcare, surveillance, sports analytics, and human-computer interaction.
Keywords: Self-Supervised Learning; Human Motion Detection; Optical Flow; Human Pose Estimation; Action Recognition; Gait Analysis; Computer Vision; Deep Learning; World-Local Flows; Joint Constraint Learning